Similar Personality Patterns Are Associated with Empathy in Four Different Countries - Melchers, Martin C.; Li, Mei; Haas, Brian W.; Reuter, Martin; Bischoff, Lena; Montag, Christian (Frontiers in Psychology, 2016)
Empathy is an important human ability associated with successful social interaction. It is currently unclear how to optimally measure individual differences in empathic processing. Although the Big Five model of personality is an effective model to explain individual differences in human experience and behavior, its relation to measures of empathy is currently not well understood. Therefore, the present study was designed to investigate the relationship between the Big Five personality concept and two commonly used measures for empathy (Empathy Quotient (EQ), Interpersonal Reactivity Index (IRI)) in four samples from China, Germany, Spain and the United States of America. This approach was designed to advance the way the Big Five personality model can be used to measure empathy. We found evidence of medium effect sizes for associations between personality and empathy, with agreeableness and conscientiousness as the most important predictors of affective and cognitive empathy (measured by the respective IRI subscales) as well as a for a one-dimensional empathy score (measured by the EQ). Empathy in a fictional context was most closely related to openness to experience while personal distress was first of all related to neuroticism. In terms of culture, we did not observe any distinct pattern concerning cultural differences. These results support the cross-cultural applicability of the Empathy Quotient and the Interpersonal Reactivity Index and indicate structurally similar associations between personality and empathy across cultures.